Comparative proteomics profiling reveals role of smooth muscle progenitors in extracellular matrix production - Simper, David; Mayr, Ursula; Urbich, Carmen; Zampetaki, Anna; Prokopi, Marianna; Didangelos, Athanasios; Saje, Angelika; Mueller, Michael; Benbow, Ulrike; Newby, Andrew C; Apweiler, Rolf; Rahman, Salman; et al. (My University, 2010)
Recent studies on cardiovascular progenitors have led to a new appreciation that paracrine factors may support the regeneration of damaged tissues.
Keywords: Angiogenesis; Extracellular matrix; Proteolytic enzymes; Proteomics; Vascular biology; Vascular muscle